Unemployment insurance and low-educated single working mothers before and after welfare reform - H. Luke Shaefer; Liyun Wu (W.E. Upjohn Institute for Employment Research, 2011)
Using the Survey of Income and Program Participation (SIPP), a nationally representative, longitudinal survey, this study examines changing levels of Unemployment Insurance (UI) eligibility and benefit receipt among working low-educated single mothers, 1990-2005. It also examines changing participation in cash welfare and the Food Stamp Program (FSP). Relative to single childless women, there has been no increase in UI benefit receipt among single mothers entering a spell of unemployment in the postreform period, even though single mothers have increased their relative rates of UI eligibility. Because of declining cash assistance receipt, UI became a more common income support than cash assistance for this population during the period 2001-2005. Furthermore, the probability of accessing FSP for low-educated single mothers entering a spell of unemployment increased in the years 2001-2005. As a result, the proportion of this population accessing benefits from one or more of these programs remained virtually unchanged across the study period.
Keywords: J65; J68; I38; 330; Welfare Reform; Unemployment Insurance; Low-educated Single Mothers